Baseline Neurocognitive Testing in Sports-Related Concussions: The Importance of a Prior Night's Sleep. (February 2014) - McClure, D. Jake; Zuckerman, Scott L.; Kutscher, Scott J.; Gregory, Andrew J.; Solomon, Gary S.
Background: The management of sports-related concussions (SRCs) utilizes serial neurocognitive assessments and self-reported symptom inventories to assess recovery and safety for return to play (RTP). Because postconcussive RTP goals include symptom resolution and a return to neurocognitive baseline levels, clinical decisions rest in part on understanding modifiers of this baseline. Several studies have reported age and sex to influence baseline neurocognitive performance, but few have assessed the potential effect of sleep. We chose to investigate the effect of reported sleep duration on baseline Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) performance and the number of patient-reported symptoms. Hypothesis: We hypothesized that athletes receiving less sleep before baseline testing would perform worse on neurocognitive metrics and report more symptoms. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We retrospectively reviewed 3686 nonconcussed athletes (2371 male, 1315 female; 3305 high school, 381 college) with baseline symptom and ImPACT neurocognitive scores. Patients were stratified into 3 groups based on self-reported sleep duration the night before testing: (1) short, <7 hours; (2) intermediate, 7-9 hours; and (3) long, ≥9 hours. A multivariate analysis of covariance (MANCOVA) with an α level of .05 was used to assess the influence of sleep duration on baseline ImPACT performance. A univariate ANCOVA was performed to investigate the influence of sleep on total self-reported symptoms. Results: When controlling for age and sex as covariates, the MANCOVA revealed significant group differences on ImPACT reaction time, verbal memory, and visual memory scores but not visual-motor (processing) speed scores. An ANCOVA also revealed significant group differences in total reported symptoms. For baseline symptoms and ImPACT scores, subsequent pairwise comparisons revealed these associations to be most significant when comparing the short and intermediate sleep groups. Conclusion: Our results indicate that athletes sleeping fewer than 7 hours before baseline testing perform worse on 3 of 4 ImPACT scores and report more symptoms. Because SRC management and RTP decisions hinge on the comparison with a reliable baseline evaluation, clinicians should consider sleep duration before baseline neurocognitive testing as a potential factor in the assessment of athletes' recovery.